Cervix cytology samples revealed increased methylation of the human markers FAM19A4/miR124‐2 up to 8 years before adenocarcinoma - Ylva Lindroth; Louise Pedersen; Jacob Alssamaray; Tim Berglund; Avalon Sundqvist; Christer Borgfeldt; Ola Forslund (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Methylation analysis of the promoter region of tumor‐suppressor genes has previously shown high sensitivity for detection of high‐grade cervical intraepithelial neoplasia (CIN) and cancer. HPV‐testing has a high sensitivity to identify women at risk to develop cancer, and has been implemented in cervical screening programs in several countries. But in most HPV‐positive women the infection will clear and they will not develop cancer. Testing for methylation could help to identify women who have potentially progressive cervical disease and need closer follow‐up. The goal of the present study was to investigate the potential use of methylation as a triage test of HPV‐positive women in the screening program. Material and methods A collection of liquid‐based cytology (LBC) samples from 106 women, collected between 4 months and 8 years before histologically confirmed cervical cancer or CIN3, was analyzed for hypermethylation of the human genes FAM19A4 and miR124‐2. Results Methylation was detected in 45% (33/73) of normal LBC samples from women who later developed CIN3+, compared with 10% (3/31) of normal LBC samples from women without subsequent dysplasia (P = 0.0006). Overall, methylation was detected in 39% (14/36), 51% (19/37), 61% (14/23) and 70% (7/10) of LBC samples from women who later developed CIN3, adenocarcinoma in situ (AIS), squamous cell carcinoma (SCC) and adenocarcinoma (ADC), respectively. Positive methylation analysis was not significantly more frequent than abnormal cytology of atypical squamous cells of unclear significance or worse (ASCUS+) in LBC samples collected 4 months to 8 years before SCC or AIS; however, prior to the development of ADC, methylation was observed in 7/10 LBC samples, despite normal cytology. Overall, LBC samples collected before invasive cancer (ADC and SCC) were more frequently positive in the methylation analysis than in cytological analysis of ASCUS+ (P = 0.048). For LBC samples collected more than 2 years before the development of AIS, SCC or ADC, methylation analysis showed a higher positivity rate than cytology did. Conclusions Testing for methylation of FAM19A4/miR124‐2 as a triage for HPV‐positive women would be useful to identify women at risk of cancer development, especially adenocarcinoma. Further studies are needed to estimate the cost‐effectiveness before introducing methylation testing in the screening program.